Brain-computer interfaces, disability, and the stigma of refusal: A factorial vignette study. (May 2023) - Sample, Matthew; Sattler, Sebastian; Boehlen, Wren; Racine, Eric
As brain-computer interfaces are promoted as assistive devices, some researchers worry that this promise to "restore" individuals worsens stigma toward disabled people and fosters unrealistic expectations. In three web-based survey experiments with vignettes, we tested how refusing a brain-computer interface in the context of disability affects cognitive (blame), emotional (anger), and behavioral (coercion) stigmatizing attitudes (Experiment 1, N  = 222) and whether the effect of a refusal is affected by the level of brain-computer interface functioning (Experiment 2, N  = 620) or the risk of malfunctioning (Experiment 3, N  = 620). We found that refusing a brain-computer interface increased blame and anger, while brain-computer interface functioning did change the effect of a refusal. Higher risks of device malfunctioning partially reduced stigmatizing attitudes and moderated the effect of refusal. This suggests that information about disabled people who refuse a technology can increase stigma toward them. This finding has serious implications for brain-computer interface regulation, media coverage, and the prevention of ableism.